Inhibition of the spread of Sclerotinia sclerotiorum in aquaponics - Biró, Györgyi; Csüllög, Kitti; Tarcali, Gábor; Fehér, Milán; Virág, Csaba István; Kutasy, Erika; Csajbók, József; Lelesz, Éva Judit (Acta Agraria Debreceniensis, 2022)
Sclerotinia sclerotiorum, which causes white mold, is a widespread pathogen. In 2020, a new host plant of this fungus, the watercress (Nasturtium officinale) was identified in Hungary in an aquaponic system. During the cultivation of watercress S. sclerotiorum was detected on the plant, the fungus caused a 30% yield loss. Fungicides should not be used against fungi in aquaponic systems. Non-chemical methods of integrated pest management should be used. These include biological control (resistant species, predators, pathogens, antagonist microorganisms), manipulation of physical barriers, traps, and the physical environment. In the aquaponic system, the removal of the growing medium (expanded clay aggregate pellets) solved the damage of Sclerotinia sclerotiorum 100%. By removing the expanded clay aggregate pellets, the environmental conditions became unfavorable for the development and further spread of the S. sclerotium fungus.